Ethical Disclosures and Good Governance: An Empirical Analysis of Firms in the Indonesian Sharia Stock Index - Vidia Gati; Kristin Juwita (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
Ethical business practices are essential for corporate sustainability, transparency, and stakeholder trust. This study examines whether companies listed on the Indonesian Sharia Stock Index (ISSI) disclose business ethics more comprehensively than non-ISSI firms. Using panel data from 1,512 firm-year observations of Indonesia Stock Exchange-listed companies during 2015–2018, the study employs independent sample t-tests and regression analysis. The findings show that ISSI-listed companies exhibit significantly higher levels of business ethics disclosure, particularly in governance-related practices. These results suggest that Sharia compliance enhances ethical transparency and supports stronger corporate governance, stakeholder trust, and long-term organizational sustainability.